β-catenin is required for taste bud cell renewal and behavioral taste perception in adult mice - Gaillard, Dany (PLoS Genet, 2017)
Taste stimuli are transduced by taste buds and transmitted to the brain via afferent gustatory fibers. Renewal of taste receptor cells from actively dividing progenitors is finely tuned to maintain taste sensitivity throughout life. We show that conditional β-catenin deletion in mouse taste progenitors leads to rapid depletion of progenitors and Shh(+) precursors, which in turn causes taste bud loss, followed by loss of gustatory nerve fibers. In addition, our data suggest LEF1, TCF7 and Wnt3 are involved in a Wnt pathway regulatory feedback loop that controls taste cell renewal in the circumvallate papilla epithelium. Unexpectedly, taste bud decline is greater in the anterior tongue and palate than in the posterior tongue. Mutant mice with this regional pattern of taste bud loss were unable to discern sweet at any concentration, but could distinguish bitter stimuli, albeit with reduced sensitivity. Our findings are consistent with published reports wherein anterior taste buds have higher sweet sensitivity while posterior taste buds are better tuned to bitter, and suggest β-catenin plays a greater role in renewal of anterior versus posterior taste buds.